Islamic Law Perspective on Good Corporate Governance and Moral Hazard Prevention in Indonesia's Insurance Sector - Faisal Faisal; Endah Atiqa Rodiah; Raden Nurhayati; Junjun Kurnia; Muhamad Dani Somantri (STAI Syaichona Moh. Cholil Bangkalan, 2025)
Corruption cases that occur in insurance companies are one of the most dangerous moral hazards that must be prevented for the sake of a healthy economic system and the implementation of good governance. The research employs a descriptive-qualitative approach in the field. Primary data were obtained through interviews, documentation, and observation, with technical analysis conducted through checking, analyzing, and comparing. The results showed that the Financial Services Authority mentored and evaluated the report on the implementation of GCG by insurance companies, as outlined in Article 79 of POJK Number 73/2016, which concerns good corporate governance for insurance companies. This is in line with the rules, which aim to eliminate the evil. The role of OJK in preventing moral hazard is carried out by providing sanctions listed in the regulations on administrative sanctions and additional sanctions, ensuring compliance with the principles of fiqh: danger must be eliminated.